Effects of Class II elastics in the treatment of Class II malocclusion - Poletto, Raquel Silva (2017)
Introduction: The objective of this study was to compare the effects of Class II malocclusion correction with Class II elastics with those produced by Class II malocclusion correction with extraoral headgear associated with multibracket appliances. Methods: A sample of 53 patients with Class II malocclusion was divided into two groups. The elastic group (EG) consisted of 26 patients who were treated with fixed appliances associated with Class II elastics. The control group (CG), consisted of 27 patients treated with fixed appliances and extraoral headgear. The groups were matched regarding initial age, treatment time, initial severity of Class II molar relationship and sex distribution. Pre- and posttreatment lateral cephalometric radiographs were evaluated. T tests were performed to compare the initial status and the treatment changes of the groups. Results: There was occlusal plane clockwise rotation in the EG. The maxillary incisors presented greater palatal tipping and retrusion and the mandibular incisor experienced smaller extrusion in the elastic than in the control group. Conclusion: Despite these small differences in treatment effects, they cannot be considered generally clinically unfavorable in every situation.